Elucidating multifaceted targets of Marein in cerebral ischemia-reperfusion injury - Luo, Weidan; Wang, Jian; Fan, Ying; Yuan, Meng; Xie, Wanying; Su, Yang; Wang, Xingchun; Zhong, Yi; Zhang, Yibo; Zhan, Jiaxin; Mao, Xuan; Huang, Xinyao; et al. (Frontiers in Chemistry, 2025)
BackgroundCerebral ischemia-reperfusion injury (CIRI) is a major pathological event in stroke, leading to neuronal damage and neuroinflammation. Marein, a flavonoid derived from Coreopsis tinctoria, has demonstrated potential neuroprotective effects, yet its precise mechanisms in CIRI remain unclear.MethodsMarein-related targets were predicted using SwissTargetPrediction, and cerebral ischemia–reperfusion injury (CIRI)-related targets were obtained from GeneCards. Common targets were identified by Venn analysis, followed by protein–protein interaction network construction and GO/KEGG enrichment analysis. Molecular docking and 100-ns molecular dynamics simulations evaluated interactions between Marein/Edaravone and key targets (PTGS2, SRC, EGFR). In vitro, an oxygen–glucose deprivation/reperfusion model in HT22 cells was used to assess cell viability, reactive oxygen species production, and protein expression.Results64 common targets (including PTGS2, SRC, EGFR) were identified. Enrichment analyses highlighted involvement in calcium signaling, inflammatory responses. Molecular docking and dynamics confirmed stable binding of Marein to PTGS2, SRC, and EGFR, with favorable binding free energies. In vitro, Marein (20 μM) improved viability of OGD/R-exposed HT22 cells, reduced ROS accumulation, and downregulated PTGS2 and SRC expression.ConclusionMarein exerts neuroprotective effects against CIRI by targeting PTGS2, SRC, and EGFR, modulating inflammatory and oxidative stress pathways. This study provides a mechanistic basis for Marein’s potential in CIRI therapy.